Pengaruh Kompensasi Dan Beban Kerja Terhadap Kinerja Karyawan Dimediasi Oleh Kepuasan Kerja : (Studi Kasus Pada PT.Sinar Bengkulu Selatan) - Nursafitri, Reza; Widodo, Slamet (Management Insight: Jurnal Ilmiah Manajemen, 2025)
The primary objective of this study is to examine the impact of compensation, workload, and performance, with job satisfaction as a mediator at PT. Sinar Bengkulu Selatan. The research employed census techniques to select participants and collected data through offline questionnaires distributed directly to PT. Sinar Bengkulu Selatan. The sample size for this study comprised 130 individuals. The analytical method used was Partial Least Square Structural Equation Modeling (PLS-SEM), executed with Smart PLS version 3.2.9 software. The study's findings reveal several significant relationships: compensation, workload, and job satisfaction all positively and significantly affect employee performance. Additionally, compensation positively and significantly influences job satisfaction. The analysis specifically indicates that workload has a negative and significant impact on job satisfaction. However, job satisfaction acts as a mediator in the relationship between compensation and performance and between workload and performance. Interestingly, job satisfaction does not mediate the relationship between workload and performance. These findings provide insight into the complex relationships among these factors within the company PT. Sinar Bengkulu Selatan